How a new fire‐suppression policy can abruptly reshape the fire‐weather relationship. Issue 10 (28th October 2015) - Ruffault, J.; Mouillot, F.
Abstract : Understanding how the interactions between anthropogenic and biophysical factors control fire regimes is increasingly becoming a major concern in a context of climate, economic and social changes. On a short time scale, fire activity is mainly driven by the variations in weather conditions. But while the assessment of this fire‐weather relationship is an essential step towards fire hazard estimations, reconstructions or projections, still little is known about the impact of human practices on this relationship. In this study, we examined the recent fire history in southern France where a new fire policy, introduced during the 1980s, suddenly brought new fire suppression and prevention practices. We aimed at assessing the impact of these changes on fire activity and on the relationships between fire and weather, usually assumed to be constant over time. To do so, we used a statistical framework based on spatially explicit daily fire occurrence data, the corresponding weather variables and the associated fuel moisture derived from a process‐based model. Our results showed that the introduction of the new fire policy resulted in a sharp decrease in fire activity but also impacted the daily fire‐weather relationship in two main ways. On the one hand, fewer wildfires ignited for similar weather conditions. On the other hand, the probability of a fire to spread over significant surfaces shifted from a fuel‐dryness driven system to a system driven by the concomitance of fuel dryness and strong winds. These observations suggest that mid‐term (decadal) social factors can affect the short‐term (seasonal to daily) relationship between weather conditions and fire activity. Thus, the interactions between human and climate factors should be taken into account when reconstructing or projecting fire activity and including the impact of fire policies on the fire‐weather relationships in fire models would be an important step towards more realistic fire regimes simulations.